2021
DOI: 10.1371/journal.pgen.1009803
|View full text |Cite
|
Sign up to set email alerts
|

A biallelic SNIP1 Amish founder variant causes a recognizable neurodevelopmental disorder

Abstract: SNIP1 (Smad nuclear interacting protein 1) is a widely expressed transcriptional suppressor of the TGF-β signal-transduction pathway which plays a key role in human spliceosome function. Here, we describe extensive genetic studies and clinical findings of a complex inherited neurodevelopmental disorder in 35 individuals associated with a SNIP1 NM_024700.4:c.1097A>G, p.(Glu366Gly) variant, present at high frequency in the Amish community. The cardinal clinical features of the condition include hypotonia, glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…In the present study, we constructed a diagnostic model of epilepsy using 23 MRGs obtained from the peripheral blood of patients with epilepsy. The model showed good diagnostic performance, as evaluated by ROC analysis (AUC = 0.8912), which was superior to that of many other epilepsy diagnosis models [41][42][43][44] .…”
Section: Discussionmentioning
confidence: 87%
“…In the present study, we constructed a diagnostic model of epilepsy using 23 MRGs obtained from the peripheral blood of patients with epilepsy. The model showed good diagnostic performance, as evaluated by ROC analysis (AUC = 0.8912), which was superior to that of many other epilepsy diagnosis models [41][42][43][44] .…”
Section: Discussionmentioning
confidence: 87%
“…We previously showed that PRC2 maintains the self-renewal of NPCs by suppressing neurogenesis 60 . This study uncovered that Snip1 and PRC2 transcriptionally regulate cell cycle progression; this may be clinically relevant to developmental defects including skull dysplasia, global developmental delay, and intellectual disability and seizure that are associated with 1097A>G (Glu366Gly) variant of SNIP1 61,62 . Our findings about the Snip1–PRC2 interactions in NPC survival and functions improves our understanding about the neurodevelopmental disorders caused by SNIP1 mutations and PRC2 dysfunction.…”
Section: Discussionmentioning
confidence: 97%
“…Clinical relevance of the SNIP1 gene has been recently documented. Homozygous 1097A>G (Glu366Gly) variant on human SNIP1 has been linked to a neurodevelopmental disorder having clinical features including skull dysplasia, global developmental delay, and intellectual disability and seizure (Ammous et al, 2021; Puffenberger et al, 2012). Our findings on the Snip1-PRC2 interaction in suppressing apoptosis and promoting neural development in the developing brain hold promise for better understanding of the neurodevelopmental disorders caused by SNIP1 mutations and PRC2 dysregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the prevalence of programmed cell death in development, the underlying mechanisms governing this process are not fully understood. Recent studies have highlighted the significance of SNIP1 in the viability of neural precursor cells and the generation of new neurons, underscoring its essential role in brain maturation [ 41 ]. Dysplasia and caspase 9-dependent apoptosis were significantly upregulated in the brain lacking SNIP1.…”
Section: Application Of Snip1 In Clinical Diseasesmentioning
confidence: 99%